Experimental study of double-panel confined masonry walls under lateral loading. (November 2018) - Belghiat, Choayb; Messabhia, Ali; Plassiard, Jean-Patrick; Guenfoud, Mohamed; Plé, Olivier; Perrotin, Pascal
Abstract: Confined masonry structures are one of the most widely used construction systems in Algeria, in which both walls and confining elements contribute to carrying the gravity and seismic loads. Several types of confining elements are used (uniform confinements, toothed confinements), each one giving the structure a different mechanical behavior while the wall density is considered as a key safety factor for those structures. The study presented in this paper is an experimental study on two types of confinement. The study originality stems from the size of the tested samples, which included double-panel confined masonry and experimental pushover tests. First, uniform masonry walls and confinements are studied. Second, toothed masonry walls consisting of two panels of Algerian clay bricks are tested. The objectives were on one hand to study the impact of the frame/panel connection on the quasi-static behavior of the structure as well as the loading and unloading behaviors. On the other hand, to highlight the impact of using double-panel walls on resisting mechanism of confined masonry walls. Moreover, the obtained data were used for evaluating the existing analytical models to predict lateral capacities of confined masonry walls. The results indicate that the two sample-types show some similar resisting mechanisms but various capacities under progressive lateral loading, which may have consequences on the seismic resistance of the structure. A mixture of shear-flexural mechanism can be noticed when double-panel walls are used. Highlights: The paper presents an experimental works for one of most building systems in Algeria. Double-panel confined masonry walls with different wall/frame connections are tested. Pushover tests are done and the correlation images technic is used in the analysis. Evaluating of some analytical models to predict lateral capacities of tested walls.